2014
DOI: 10.3126/jkmc.v2i1.10512
|View full text |Cite
|
Sign up to set email alerts
|

Disparties in fruit and vegetable intake by Socio-demographic characteristics in peri-urban Nepalese adults: findings from the Heart-health Associated Research and Dissemination in the Community (HARDIC) Study, Bhaktapur, Nepal

Abstract: Background: Inadequate fruit and vegetable intake and other adverse dietary habits -along with tobacco and alcohol abuse and sub-optimal physical activity -make up the four most important behavioural risk factors of non-communicable diseases. Low fruit and vegetable intake is particularly associated with burden of high cardiovascular disease. It has received more attention in the last decade, with studies that explore disparities and determinants in their intake, as well as interventions that attempt to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…This suggests an urgent need for public health interventions, although local context needs to be particularly considered for this risk factor. This finding is similar to the findings of another study conducted among in a peri-urban population in Nepal, which found that about 98% of the study population consumed less than the recommended 5 servings daily of fruits and vegetables [ 28 ]. The prevalence of low fruit and vegetable intake is increasing compared to the previous STEPS survey in 2007/08, however, again this difference could be due to a difference in sampling methods between the two surveys [ 8 ] as there are contradictory reports of increased per capita vegetable consumption in the last two decades [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…This suggests an urgent need for public health interventions, although local context needs to be particularly considered for this risk factor. This finding is similar to the findings of another study conducted among in a peri-urban population in Nepal, which found that about 98% of the study population consumed less than the recommended 5 servings daily of fruits and vegetables [ 28 ]. The prevalence of low fruit and vegetable intake is increasing compared to the previous STEPS survey in 2007/08, however, again this difference could be due to a difference in sampling methods between the two surveys [ 8 ] as there are contradictory reports of increased per capita vegetable consumption in the last two decades [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…JD-HDSS aims to collect longitudinal data on the health status of this peri-urban community, with particular focus on cardiovascular health. 13 The prevalence of cardiovascular risk factors such as low fruit and vegetable consumption in JD-HDSS is high, 14 and cardiovascular health knowledge, attitude and practice/behaviour is poor. 15 Although unhealthy diet is a known cause of CVDs, our in-depth interviews with people affected by cardiometabolic diseases revealed frequent common misconceptions regarding the components of a healthy diet.…”
Section: Introductionmentioning
confidence: 99%
“…The per capita vegetable consumption of Nepal increased from 60 kg to 105 kg in last two decades [2]. However, fruit and vegetable consumption in Nepal is still below the WHO recommended level [4]. Chitwan district is one of the consistent vegetable suppliers for the major vegetable market of the country including the capital city, Kathmandu.…”
Section: Introductionmentioning
confidence: 99%